Economic Feasibility of Solar Irrigation Pumps: A Study of Northern Bangladesh - Md. Tawhidul Islam; Md. Elias Hossain (International Journal of Renewable Energy Development, 2022)
Bangladesh is the most densely populated country in the world. With a total population of around 165 million, the country has constantly been facing food security challenges and other problems. Therefore, increasing food production is one of the feasible solutions to this challenge, and proper agricultural land use for food production bears critical importance. Adopting sustainable irrigation systems and viable technologies would be vital for ensuring efficient use of agricultural land in Bangladesh to safeguard the country's food security. Solar irrigation pumps (SIPs) can be a reliable option in this regard. However, Bangladesh has experienced a prolonged growth rate of SIP installation in the last decade.  The countryhas set a target to install 10000 SIPs by the year 2027, albeit it is a tiny share of the 1.57 million conventional irrigation pumps operating in the country. This study aims to investigate the economic feasibility of the SIPs operating in the northern region of Bangladesh in terms of estimating financial feasibility and environmental benefits. The study is mainly based on primary data collected from the users of SIPs from two Upazilas of Dinajpur and Rangpur districts. A total of 14 SIPs, categorized into large, medium, and small pumps, are selected randomly from the available SIPs in the study areas. The financial analysis reveals that small SIPs are the most profitable option (20% IRR) for investment. Large SIPs are moderately profitable (10% IRR), and their profitability can be improved (10.50% IRR) by introducing additional uses of solar energy. However, medium SIPs are the worst (5% IRR) option for investment. In the study areas, large and medium SIPs are designed for the 'fees for service model', and small SIPs are designed for the 'fees for ownership model'. It is found that the 'fees for ownership model' is more profitable than the 'fees for service model'. Moreover, the net environmental benefit for all SIPs is found almost equal to the given subsidy for installing them. Also, the net environmental benefit per kilowatt peak (kWp) is highest for the small SIPs. This paper recommends that additional use (e.g., husking, grinding, supply excess electricity to grid, and so on) of solar energy can improve the profitability of investmenton SIPs. Further, the government should continue giving grants for installing SIPs and promote 'fees for ownership model' (small SIPs) for personal use. It would speed up the dissemination rate of SIPs and help increase the country's agricultural production and improve the environmental conditions.